A polyoxometalate‐based metal–organic polyhedron constructed from a V5O9Cl building unit with rhombicuboctahedral geometry - Gong, Ya-Ru; Su, Zhong-Min; Wang, Xin-Long (Acta crystallographica. Section C, Crystal structure communications, 2018)
The design and construction of metal–organic polyhedra has received much attention by chemists due to the intriguing diversity of architectures and topologies that can be achieved. There are several crucial factors which should be considered for the construction of metal–organic polyhedra, such as the starting materials, reaction time and temperature, solvent and suitable organic ligands. Recently, polyoxometalates (POMs), serving as secondary building units to construct POM‐based metal–organic polyhedra, have been the subject of much interest. The title compound, dodecakis(dimethylammonium) octakis(μ‐benzene‐1,3,5‐tricarboxylato)hexa‐μ‐chlorido‐tetracosa‐μ‐oxido‐triacontaoxidotriacontavanadium, (NH2Me2)12[(V5O9Cl)6(C9H3O6)8], was synthesized successfully by self‐assembly of VOCl3 and benzene‐1,3,5‐tricarboxylic acid under solvothermal conditions. The title polyhedron has an rdo topology when the V5O9Cl building unit and the benzene‐1,3,5‐tricarboxylate (BTC3−) ligand were simplified into 4‐connected and 3‐connected vertices. Interestingly, when the V5O9Cl building unit and the BTC3− ligand are considered as quadrangular and triangular faces, the structure displays rhombicuboctahedral geometry with an outer diameter of 21.88 Å. The packing of the polyhedra produces a circular channel with a diameter of 8.2 Å. The title compound was characterized by single‐crystal X‐ray diffraction, elemental analysis, IR spectroscopy, thermogravimetric analysis and powder X‐ray diffraction. A new polyoxovanadate‐based metal–organic polyhedron with an rdo topology was constructed from a V5O9Cl building unit and benzene‐1,3,5‐tricarboxylic acid under solvothermal conditions. The title compound displays rhombicuboctahedral geometry when the polyoxovanadate building units and organic ligands were considered as the quadrangular and triangular faces of a polyhedron.